2016
DOI: 10.1111/inm.12208
|View full text |Cite
|
Sign up to set email alerts
|

Physical health nurse consultant role to improve physical health in mental health services: A carer's perspective

Abstract: The physical health of people diagnosed with a mental illness is significantly poorer in comparison with the general population. Awareness of this health disparity is increasing; however, strategies to address the problem are limited. Carers play an important role in the physical health care of people with mental illness, particularly in facilitating navigation of and advocating in the health care system. A specialist physical health nurse consultant position has been suggested as a way to address the physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…Carers required additional support from health services in order to support behaviour change interventions; and expressed a need for health services to provide more holistic care for people with a mental illness. Carers in this study, and previous research, have identified a need for services to provide additional support in the form of increased information and collaboration to assist them in supporting family members in risk behaviour change [ 41 , 46 , 78 ]; as well as additional information and behaviour change support being provided directly to their family members [ 46 , 59 , 78 ]. The finding that carers’ awareness of their family member’s risk behaviours and ability to support or encourage behaviour change was often contingent on whether or not they resided together, suggests that when collaborating with carers, mental health services should ensure behaviour change support and advice is appropriate for the carer’s particular circumstances and the dynamics of the caring relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Carers required additional support from health services in order to support behaviour change interventions; and expressed a need for health services to provide more holistic care for people with a mental illness. Carers in this study, and previous research, have identified a need for services to provide additional support in the form of increased information and collaboration to assist them in supporting family members in risk behaviour change [ 41 , 46 , 78 ]; as well as additional information and behaviour change support being provided directly to their family members [ 46 , 59 , 78 ]. The finding that carers’ awareness of their family member’s risk behaviours and ability to support or encourage behaviour change was often contingent on whether or not they resided together, suggests that when collaborating with carers, mental health services should ensure behaviour change support and advice is appropriate for the carer’s particular circumstances and the dynamics of the caring relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The new norm will need to be considered at all levels of pre-and postregistration training. Notably, the emotional labour (anxiety, fear and stress) associated with this new norm described by some participants in this study is understandable given nurses primarily focus on mental health rather than physical health, although this positioning is being increasingly challenged (Happell, Gaskin, et al, 2016a;Happell, Wilson, et al, 2016b).…”
Section: Discussionmentioning
confidence: 90%
“…Further, nurses are the most likely "first responders" to acute physiological deterioration (APD) in mental health units (Porter, Cant, Missen, Raymond, & Churchill, 2018). The combined mental state acuity and the emerging recognition of the increased risk of physical health acuity in this group has placed nurses in particular in a challenging position where they are required to have high levels of confidence and skills across both domains (Ehrlich et al, 2014;Happell, Wilson, Platania-Phung, & Stanton, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some experiences with SMD patients with physical comorbidities treated in the US Medicaid system based on a nurse-navigator model have shown promising results in the seamless management of mental and physical health problems [ 34 ]. However, for these services to be effective, a solid and consistent approach is required, with well-defined limits and sufficient resolution capacity to bridge the various gaps that arise throughout the process [ 35 ]. Ryvicker's [ 36 ] behavioral-ecological conceptual framework for navigation addresses these two requirements.…”
Section: Introductionmentioning
confidence: 99%